Challenges of labour : Central and Western Europe, 1917-1920 - Wrigley, Chris (Routledge, 1993)
Much of Europe experienced or was on the verge of revolution in 1917-20. These essays written by renowned European scholars, provide a comprehensive survey of how the forces of order and property crushed most of the socialist forces.